Parking demand during daytime at rest and service area along north-south expressway - Izzul Ramli, 1988-, author; Siti Asmah Hassan, supervisor; Mohd. Rosli Hainin, 1961-, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2020